Morbidity, mortality and quality of life in the ageing haemodialysis population: results from the ELDERLY study - Seckinger, Jörg; Dschietzig, Wilfried; Leimenstoll, Gerd; Rob, Peter M.; Kuhlmann, Martin K.; Pommer, Wolfgang; Fraass, Uwe; Ritz, Eberhard; Schwenger, Vedat (Clinical kidney journal, 2016)
The physical - functional and social - emotional health as well as survival of the elderly (≥75 years of age) haemodialysis patient is commonly thought to be poor. In a prospective, multicentre, non-interventional, observational study, the morbidity, mortality and quality of life (QoL) in this patient group were examined and compared with a younger cohort.